Pengaruh Kompetensi dan Kompensasi Terhadap Kinerja Karyawan (Studi pada Karyawan PT. BPR Panji Aronta Jombang) - Deni Widyo Prasetyo (Fakultas Ekonomi Universitas Yos Soedarso, 2023)
The purpose of this study was to determine the effect of competence, and compensation variables on the performance of employees of PT. BPR Panji Aronta. Data collection was carried out by distributing questionnaires, interviews, observations, and documentation. This study uses a quantitative approach with explanatory research methods which are carried out through data collection in the company. The population used is PT.BPR Panji Aronta employees, totaling 31 employees. The sampling technique used was the saturated sample technique. The data analysis method used validity test, reliability test, classical assumption test, multiple linear regression analysis, hypothesis testing through t test and coefficient of determination (r2). This study obtained the results that work discipline has a positive and significant effect on employee performance, while organizational commitment has a positive and significant effect on employee performance at PT. BPR Panji Aronta. Keywords: Competence; Compensation; Employee Performance.